Problematika Pembuktian Digital dalam Penegakan Hukum Tindak Pidana Siber di Indonesia - Eka Fitri Lestari; Rahmayanti Rahmayanti; Donly Calner Aruan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The development of information and communication technology has accelerated digital transformation, but it has also led to increasingly complex cybercrimes. The characteristics of cybercrime—anonymity, cross-jurisdictional nature, and reliance on electronic systems—make evidentiary processes a major challenge in criminal law enforcement in Indonesia. In this context, electronic evidence and digital forensics play a crucial role in uncovering crimes and linking perpetrators to criminal acts. Although electronic information and documents have been legally recognized as evidence under the Law on Electronic Information and Transactions, their implementation still faces various challenges. This study aims to analyze the legal framework of digital evidence, identify existing obstacles, and formulate strategies to optimize digital proof systems in criminal law enforcement. The research employs a normative legal method with statutory, conceptual, and case approaches. The findings reveal key challenges, including the volatility of electronic evidence, limited human resources and digital forensic infrastructure, lack of standardized procedures, difficulties in obtaining data from electronic service providers, and jurisdictional barriers due to the transnational nature of cybercrime. Additionally, differing interpretations among law enforcement officers regarding the validity and integrity of electronic evidence remain an issue. To address these challenges, efforts are needed to strengthen regulations, enhance institutional capacity, standardize digital forensic practices, improve inter-agency coordination, and expand international cooperation